2021
DOI: 10.3390/ijerph18105352
|View full text |Cite
|
Sign up to set email alerts
|

The Magnifying Effect of Marital Satisfaction on the Dyadic Effect of Disabilities on Life Satisfaction

Abstract: (1) Background. Extending previous work, the present study examined whether marital satisfaction would magnify the dyadic effect of disabilities on life satisfaction among older married couples. (2) Methods. With responses collected from 11,694 participants (5847 couples; Mage = 63.36 years, median: 62 years) in a large-scale survey study in China in 2015, the actor-partner interdependence model (APIM) analyses were conducted to examine how marital satisfaction moderated the actor and partner effects of disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Moreover, the depression levels of both members of a couple were found to have a significant interaction in this study, but the same effect was not observed for their anxiety levels. In another study, marital satisfaction amplified the negative relationship between disability and life satisfaction as a moderator [ 6 ]. Most previous studies on the relationship between marital satisfaction and depressive symptoms have focused on the actor effect; nonetheless, the partner effect has also been increasingly investigated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the depression levels of both members of a couple were found to have a significant interaction in this study, but the same effect was not observed for their anxiety levels. In another study, marital satisfaction amplified the negative relationship between disability and life satisfaction as a moderator [ 6 ]. Most previous studies on the relationship between marital satisfaction and depressive symptoms have focused on the actor effect; nonetheless, the partner effect has also been increasingly investigated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, marriage is the foundation of society and, in recent times, with the rapid change of social values, the institution of marriage is undergoing significant changes (Lavner et al, 2018). Over the years, the quality of marital relationships has been examined in terms of "satisfaction," "adaptation," "conformity," and/or "happiness," and sometimes these terms have been used as complementary elements of marital quality (Li & Jiang, 2021) . Marital adjustment is a key factor in good family functioning, facilitating parental roles and promoting economic growth and greater life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…일부 부부관계와 건강상태 간의 관계에서 건강행동의 매개효과를 보고한 연구들 (Lee et al, 2021;Roberson et al, 2018) (Bookwala & Schulz, 1996;Peek et al, 2006;Powdthavee, 2009). 뿐만 아 니라 부부관계와 건강상태는 자기 자신과 상대방의 웰빙에도 영 향을 미치는 것으로 보고되었다 (Ayotte et al, 2010;Bourassa et al, 2015;Joo & Jun, 2014;Lee et al, 2021;Li & Jiang, 2021;Min et al, 2020;Ruthing et al, 2012;Valle et al, 2013). 이는 건강상태 저하로 겪는 부정적 정서가 부부간에 전이 되며 (Siegel et al, 2004), 부부의 웰빙은 상호의존적이기 때문 (Bookwala & Schulz, 1996)이라고 볼 수 있다.…”
unclassified
“…또한 부부의 삶의 만족도를 예측하는 부부의 건강상태는 부부관 계의 질에 영향을 받는데, 부부관계의 질은 서로의 건강 증진행동 또는 건강 위험행동을 증가시킨다 (Cohen, 2004;Lee et al, 2019;. 그리고 이는 신체의 생리적인 변화로 이 어져 (Kiecolt-Glaser & Wilson, 2017), 서로의 건강상태에 영향을 준다 (Kiecolt-Glaser & Glaser, 2002;Lee et al, 2021;Nealey-Moore et al, 2007;Wickrama et al, 2001) (Li & Jiang, 2021;Min et al, 2020;Monin et al, 2015;Pinquart & Sörensen, 2011;Walker & Luszcz, 2009) 3) 매개변수 1: 건강행동 , 1991;Lee et al, 2019;Whisman et al, 2006) (House et al, 1988;Kiecolt-Glaser & Newton, 2001;South & Krueger, 2013;Uchino, 2004). 이러한 관계는 높은 부부관계의 만족도에 따른 긍정적인 심리적 반응이 만들어 내는 생리적 반응을 기초로 이해할 수 있다.…”
unclassified